Resection of colorectal liver metastases after second-line chemotherapy: is it worthwhile? A LiverMetSurvey analysis of 6415 patients. (June 2017) - Adam, René; Yi, Bin; Innominato, Pasquale F.; Barroso, Eduardo; Laurent, Christophe; Giuliante, Felice; Capussotti, Lorenzo; Lapointe, Réal; Regimbeau, Jean-Marc; Lopez-Ben, Santiago; Isoniemi, Helena; Hubert, Catherine; et al.
Abstract: Purpose: Patient outcome after resection of colorectal liver metastases (CLM) following second-line preoperative chemotherapy (PCT) performed for insufficient response or toxicity of the first-line, is little known and has here been compared to the outcome following first-line. Patients and methods: From January 2005 to June 2013, 5624 and 791 consecutive patients of a prospective international cohort received 1 and 2 PCT lines before CLM resection (group 1 and 2, respectively). Survival and prognostic factors were analysed. Results: After a mean follow-up of 30.1 months, there was no difference in survival from CLM diagnosis (median, 3-, and 5-year overall survival [OS]: 58.6 months, 76% and 49% in group 2 versus 58.9 months, 71% and 49% in group 1, respectively, P  = 0.32). After hepatectomy, disease-free survival (DFS) was however shorter in group 2: 17.2 months, 27% and 15% versus 19.4 months, 32% and 23%, respectively ( P  = 0.001). Among the initially unresectable patients of group 1 and 2, no statistical difference in OS or DFS was observed. Independent predictors of worse OS in group 2 were positive primary lymph nodes, extrahepatic disease, tumour progression on second line, R2 resection and number of hepatectomies/year <50. Positive primary nodes, synchronous and bilateral metastases were predictors of shorter DFS. Initial unresectability did not impact OS or DFS in group 2. Conclusion: CLM resection following second-line PCT, after oncosurgically favourable selection, could bring similar OS compared to what observed after first-line. For initially unresectable patients, OS or DFS is comparable between first- and second-line PCT. Surgery should not be denied after the failure of first-line chemotherapy. Highlights: A heavier tumour burden was found in patients with colorectal liver metastases (CLM) resection after 2nd-line preoperative chemotherapy (PCT). The 49% 5-year overall survival (OS) from CLM diagnosis in this group was similar to that after 1st-line. OS or disease-free survival was comparable for the subsets of initially unresectable of two PCT groups. Surgery of CLM may be proposed to resect CLM ever after 2nd-line chemotherapy.